Service quality assessment of transportation and government services: a study of the Hong Kong tourism industry - Tukamushaba, Eddy K.; George, Babu P. (International Journal of Hospitality and Event Management, 2014)
This paper presents the results of a study examining service quality assessment of selected sectors of the Hong Kong tourism industry. The functioning of three related sectors of air, rail, and road transport, as well as tourism related government departments, is considered. Identification of the visitors and their perceptions of quality of service offered by these sectors are examined. In order to establish the importance of each of the service quality attributes in determining each sector’s performance, importance-performance analysis was conducted on the airlines, public transport, and government agencies such as police, immigration, customs, and leisure and cultural services. The implications of the results obtained are discussed
Keywords: service quality; satisfaction; loyalty; tourism